2017
DOI: 10.1002/1873-3468.12582
|View full text |Cite
|
Sign up to set email alerts
|

Processing of PatS, a morphogen precursor, in cell extracts of Anabaena sp. PCC 7120

Abstract: Upon N-stepdown, Anabaena sp. PCC 7120 differentiates heterocysts along filaments in a semiregular pattern. A 17-amino acid peptide called PatS is a morphogen precursor for pattern formation. The principal PatS derivative involved in heterocyst patterning has been proposed to be the C-terminal peptide PatS-5 (RGSGR), PatS-6 (ERGSGR), or PatS-8 (CDERGSGR). We present the first evidence for processing of PatS in cell extracts of this cyanobacterium. PatS is probably cleaved between the C-terminal 7th and 8th ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Resolution of clusters is achieved by lateral inhibition effected by PatS, whose production is induced by HetR early after nitrogen step-down. The gene patS encodes a short peptide whose C-terminal domain is post-transcriptionally processed to yield the hepta-peptide PatS-7 with the sequence RGSGR, which is believed to diffuse to neighboring cells [ 13 , 14 ]. There, it interferes with the DNA-binding activity of HetR and causes its degradation, creating HetR gradients along filaments [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resolution of clusters is achieved by lateral inhibition effected by PatS, whose production is induced by HetR early after nitrogen step-down. The gene patS encodes a short peptide whose C-terminal domain is post-transcriptionally processed to yield the hepta-peptide PatS-7 with the sequence RGSGR, which is believed to diffuse to neighboring cells [ 13 , 14 ]. There, it interferes with the DNA-binding activity of HetR and causes its degradation, creating HetR gradients along filaments [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed that PatS-8 is processed to the shorter PatS-5 and PatS-6, which then might diffuse along the filament (Zhang et al. 2017 ). Expression of the full-length patS from Anabaena sp.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, PknH might be related to processing the HetN protein. It has been reported that there were PatS-processing activities within cell extracts of Anabaena [ 31 ]. patS encodes a protein with 17 amino acids [ 11 ], but the PatS C-terminal hexapeptide (ERGSGR) has been proposed to be an active form of PatS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%